SAT-LB005 Association of Serum Estrogens and Estrogen Metabolites with Use of Non-Steroidal Anti-Inflammatory Drugs in Postmenopausal Women - Fuhrman, Barbara (J Endocr Soc, 2019)
Background: In several recent studies of postmenopausal women, the use of non-steroidal anti-inflammatory drugs (NSAIDs) has been associated with lower circulating estrogens. These analgesics have also been studied in association with breast cancer risks with inconsistent findings. Cross-talk between immune and endocrine factors may play important roles in the development of breast cancer. Methods: We conducted a study of postmenopausal women drawn from the Prostate, Lung, Colon and Ovarian Cancer Screening Trial cohort (PLCO). At study baseline, participants reported their frequency of use for aspirin, non-aspirin NSAIDs via questionnaire. High-performance liquid chromatography-tandem mass spectrometry was used to measure estrogens and estrogen metabolites (EM) in baseline serum samples from 354 women who went on to get breast cancer during study follow-up, and 423 women who remained healthy. All selected participants reported no use of menopausal hormones at study baseline. General linear models were used to estimate multivariable-adjusted mean EM by self-reported use of analgesics (daily, weekly, or less than weekly) in all participants, while adjusting for continuous age, baseline BMI and breast cancer outcome. Results: In comparison to women who reported that they did not use any NSAIDs on a daily basis, those reporting daily use of aspirin only, daily use of non-aspirin NSAIDs only and daily use of both aspirin and non-aspirin NSAIDs had lower multivariable adjusted serum concentrations of unconjugated estradiol (Pdiff<0.02). Greater frequency of non-aspirin NSAID use was associated with trends towards lower concentrations of total EM (Ptrend=.004), estrone (Ptrend=.004), and unconjugated estradiol (Ptrend=.04), and higher ratios of 2- and 4- hydroxylated EM to the parent estrogens (Ptrend=.02 and .04). Associations were similar in women who did and did not go on to have breast cancer. Discussion: In this sample of postmenopausal women, more frequent use of NSAIDs was associated with lower circulating estrogens and with patterns of estrogen metabolism that may be more favorable with respect to breast cancer risk. These results require independent confirmation in additional well-designed studies. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.